METAL OXIDE COMPOUND OF DOUBLE PEROVSKITE SR2TICO(1-X)FEXO6 : LATTICE ENERGY CALCULATION, SYNTHESIS, AND STRUCTURAL ANALYSIS - Ramadhany, Adhiena
Heat waste could be used as the new source of electrical energy by utilizing thermoelectric phenomenon. This study comprises of synthesizing the promising thermoelectric material of the solid solution of double perovskite Sr2TiCoO6 with Sr2TiFeO6, studying the compounds stability and performing structural analysis of the compounds via solid-state synthesis. Lattice energy calculation to scrutinize the compounds stability based on the chemical bond theory which consist of both ionic and covalent bonds contributing to the lattice were performed. This method can be applied from simple binary compounds, ternary compounds and then to Sr2TiCo(1-x)FexO6 (ST(CF)O). Synthesis of the those compounds are carried out by the solid state method. The compounds are synthesized in molar ratio of Co:Fe = 1:0, 0.5:0.5, and 0:1, which are calcined for 12 hours at 900 ?C, then sintered in a form of individual pellet for total of 36 hours at 1000?C. As-sintered samples were characterized with powder X-ray diffraction and the structural analysis on diffraction pattern of the samples are done by means of Rietveld method with pseudo-Voigt function. For ST(CF)O that were synthesized, showed the existence of two-phases on each sample which has increasing in lattice parameter value as x increased, and in accordance with the Vegard’s Law. Both phases are showing similar reflective plane, therefore, both phases have the same Pm-3m space group. In regard to the lattice energy calculation, we found out that the stability of ST(CF)O are consistent with the lattice energy of SrTiO3 the value of ~17,000 kJ/mol and are decreasing as the increasing of x. For SrTiCo(1-x)FexO6, the increasing of x leads to the increasing of lattice parameter a, decreasing of peak width (FWHM), increasing of dominant phase intensity and decrease of lattice energy. Lattice energy of the compound can be correlated to each respective bond strength as the change of lattice parameter in cubic Pm-3m directly affect bond lengths.